(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2026)
The 16th Ebola outbreak in the Kasai Province of the Democratic Republic of Congo in September 20205 renewed palpable fears of a possible spread of the deadly virus to West Africa, especially in Nigeria, where the outbreak of 2014 seriously disrupted mostly Small and Medium-sized Enterprises (SMEs) that are yet to recover from the impact. In an increasingly globalised world, interconnected by land, air, and sea, pandemics in one remote country can spread quickly and disrupt the supply chains in far-flung locations, leading to disastrous social and economic consequences for commercial transactions, especially SMEs. They drive innovation and create more jobs than the public service, but are prone to layoffs and construction. Luckily, the latest outbreak was promptly contained to the relief of global disease-tracking agencies. As one advertisement on the Cable News Network (CNN) declares: Everything is connected to business, just as business is connected to everything else. In Nigeria, these pandemics significantly disrupted the already struggling Small and Medium-sized Enterprises (SMEs), resulting in lower productivity, substantial financial losses, and increased unemployment, with dire consequences for the government and the rest of society. The WHO identifies weak healthcare systems, poor access to quality healthcare, and atavistic cultural norms as contributing factors to the spread of HIV/AIDS, Ebola, and COVID-19 in many developing nations. The study relies on quantitative approaches and secondary data to highlight the negative impact of global pandemics on SMEs in Nigeria, especially the challenges they faced during and after the outbreaks. The paper proposes more effective and inclusive strategies to reduce the adverse effects of future pandemics on SMEs, including reinforcing digital infrastructure to minimise human contact, sourcing contingency funding, and government support at all levels to keep SMEs functional and profitable, even in crises.